Dermatomyositis Associated with Myelofibrosis following Polycythemia Vera - Naomi Fei; Sarah Sofka (Case Reports in Hematology, 2017)
Dermatomyositis (DM) is a unique inflammatory myopathy with clinical findings of proximal muscle weakness, characteristic rash, and elevated muscle enzymes. The association of DM and malignancy, most commonly adenocarcinoma, is well known. There have been few case reports of primary myelofibrosis associated with DM. We present the case of a 69-year-old male with a history of polycythemia vera (PV) who developed proximal muscle weakness, dysphagia, and rash. He was found to have elevated creatinine kinase and skin biopsy was consistent with DM. Due to persistent pancytopenia a bone marrow biopsy was performed and showed postpolycythemic myelofibrosis. To our knowledge, this is the first case reported of this unique association.